Clinicopathological features of homologous recombination deficient epithelial ovarian cancers: sensitivity to PARP inhibitors, platinum and survival - Mukhophadyay, Asima; Plummer, Elizabeth R; Elattar, Ahmed; San, SooHoo; Uzir, Bisha Fathamah; Quinn, Jennifer E; Edmondson, Richard J; Curtin, Nicola J; Harriet, Aneke; Maxwell, Perry; McCluggage, W Glenn (American Association of Cancer Research, 2012)
Up to 50% of epithelial ovarian cancers (EOC) display defects in the homologous recombination (HR) pathway. We sought to determine the ramifications of the homologous recombination deficient (HRD) status on the clinicopathological features, chemotherapy response and survival outcomes of EOC patients. HR status was determined in primary cultures from ascitic fluid in 50 chemotherapy naïve patients by a functional RAD51 immunofluorescence assay and correlated with in vitro sensitivity to the PARP inhibitor (PARPi), rucaparib. All patients went on to receive platinum based chemotherapy; platinum sensitivity, tumor progression and overall survival were compared prospectively in HR competent vs. HR deficient patients. Compared to HR competent patients, the HRD group was predominantly serous with a higher median CA125 at presentation. HRD was associated with higher ex vivo PARP inhibitor sensitivity and clinical platinum sensitivity. Median follow up duration was 14 months; patients in the HRD group had lower tumor progression rates at 6 months, lower overall /disease specific death rates at 12 months and higher median survival. We therefore suggest that HRD as predicted by a functional RAD51 assay correlates with in vitro PARPi sensitivity, clinical platinum sensitivity and improved survival outcome.